Person-centred care in complementary medicine for individuals with chronic conditions in Australia. (30th September 2020) - Foley, H; Steel, A; Adams, J
Abstract: Background: Increasing chronic condition diagnoses burden public health systems, individuals and communities. The duration and complexity of chronic conditions require ongoing, multifaceted care - such as person-centred care (PCC) - to address the individual needs and quality of life for patients. Many patients with chronic conditions seek additional care outside mainstream medicine, often consulting complementary medicine (CM) practitioners. This study examines the extent of PCC being experienced by patients with chronic conditions who consult CM practitioners. Methods: Cross-sectional survey (n = 191), conducted nationally, November 2018 to March 2019, in clinics of the five CM professions most commonly consulted by individuals with chronic conditions in Australia (massage, chiropractic, osteopathy, acupuncture, naturopathy). Participants with chronic conditions (n = 153) were surveyed about experiences of PCC during CM consultation, and regarding consultation with medical doctors, using four validated measures. Results: During consultation with CM practitioners, patient perceptions of PCC were consistently high. Ratings of PCC were consistently higher for consultations with any CM practitioners (summary mean 3.33) than consultations with medical doctors (summary mean 2.95). The highest mean scores for PCC were reported by patients of naturopaths (summary mean 4.04). Variations in perceived PCC for different items between professions indicate nuance in the experience of consultation across different CM professions. Conclusions: This study indicates PCC is characteristic of CM consultation, which may reflect CM philosophies such as holism. CM practitioners may present an existing resource of PCC. Further attention should be given to CM professions regarding the potential to address unmet needs of individuals with chronic conditions, and subsequently to better manage the public health burden associated with chronic conditions. Key messages: Person-centred care appears to be a consistent characteristic of complementary medicine clinical care for individuals with chronic conditions. Due to rising rates of chronic conditions and the associated burden on public health systems, complementary medicine professions should be considered as a resource to optimise chronic illness care.